Environmental concentrations of some of the major inorganic pollutants at the BARC site, Trombay, Bombay - ZUTSHI, P. K.; SEQUEIRA, R.; MAHADEVAN, T. N.; BANERJEE, TAPOTI (MAUSAM, 1970)
Aggregate monthly averages of some of the major inorganic pollutants in the atmosphere, at the BARC site at Trombay. Bombay over the past few years are presented. With a view to broadly assess the extent of air pollution at the sampling site, the results are compared with known international air quality standards.